The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2022
DOI: 10.1038/s41598-022-10565-6
|View full text |Cite
|
Sign up to set email alerts
|

Twisted intramolecular charge transfer of nitroaromatic push–pull chromophores

Abstract: The structural changes during the intramolecular charge transfer (ICT) of nitroaromatic chromophores, 4-dimethylamino-4′-nitrobiphenyl (DNBP) and 4-dimethylamino-4′-nitrostilbene (DNS) were investigated by femtosecond stimulated Raman spectroscopy (FSRS) with both high spectral and temporal resolutions. The kinetically resolved Raman spectra of DNBP and DNS in the locally-excited and charge-transferred states of the S1 state appear distinct, especially in the skeletal vibrational modes of biphenyl and stilbene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 96 publications
0
10
0
Order By: Relevance
“…Previous calculations showed that hydrogen transfer from the aci -tautomer back to o -nitrophenol (2NP) is effectively barrierless in the electronic ground state [ 14 ], so conversion to the aci -tautomer and relaxation to the ground state would allow for efficient conversion back to the original molecule, especially in methanol because the lengthened HGS relaxation may allow this step to occur. The definitive determination of whether ESIPT occurs in either solvent could inspire future experimental and/or computational work, possibly on excited-state FSRS characterization [ 51 , 86 , 88 ], which underlies the importance of fundamental mechanisms and potential applications for these environmentally relevant molecules to achieve desirable outcomes and societal benefits. In essence, we envision the systematic characterization of nitrophenols and nitrophenolates in water and alcohol (methanol) in this comprehensive work to lay a solid foundation for future steady-state and time-resolved (particularly ultrafast) spectroscopies of these environmentally relevant small molecules in condensed phase, including both excited-state FSRS [ 54 , 75 , 78 ] and its time-domain analogue (impulsive Raman or ISRS (impulsive stimulated Raman scattering) [ 89 , 90 , 91 ]).…”
Section: Discussionmentioning
confidence: 99%
“…Previous calculations showed that hydrogen transfer from the aci -tautomer back to o -nitrophenol (2NP) is effectively barrierless in the electronic ground state [ 14 ], so conversion to the aci -tautomer and relaxation to the ground state would allow for efficient conversion back to the original molecule, especially in methanol because the lengthened HGS relaxation may allow this step to occur. The definitive determination of whether ESIPT occurs in either solvent could inspire future experimental and/or computational work, possibly on excited-state FSRS characterization [ 51 , 86 , 88 ], which underlies the importance of fundamental mechanisms and potential applications for these environmentally relevant molecules to achieve desirable outcomes and societal benefits. In essence, we envision the systematic characterization of nitrophenols and nitrophenolates in water and alcohol (methanol) in this comprehensive work to lay a solid foundation for future steady-state and time-resolved (particularly ultrafast) spectroscopies of these environmentally relevant small molecules in condensed phase, including both excited-state FSRS [ 54 , 75 , 78 ] and its time-domain analogue (impulsive Raman or ISRS (impulsive stimulated Raman scattering) [ 89 , 90 , 91 ]).…”
Section: Discussionmentioning
confidence: 99%
“…32,36 Photoexcitation of push-pull NSBs into their S 1 state is believed to produce an intramolecular CT state, whose deactivation dynamics dictates the fluorescence behaviors and is complicated by the competition among several major pathways, including (1) barrier crossing along the central ethylenic bond torsion to a roughly perpendicular configuration ( 1 p*), (2) formation of the twisted intramolecular charge-transfer (TICT) states with respect to one or more twisting coordinates, and (3) ISC to the triplet-state manifold followed by isomerization and/or other nonadiabatic transitions. 32,[36][37][38][39][40][41][42][43] The dipole moments and fluorescence properties of various stationary states involved in these pathways are believed to be quite different. Consequently, the solvent polarity can modulate the energy profile of deactivation pathways, resulting in strong solvent-dependent fluorescence and photochemical behaviors.…”
Section: Introductionmentioning
confidence: 99%
“…3,27 On the other hand, the introduction of the CN double bond to a position with a large LUMO coefficient may result in a small HOMO-LUMO energy gap and enhance intramolecular chargetransfer (ICT) transition. [28][29][30] The reduction of the HOMO-LUMO energy gap is favorable for light-based organic semiconductor applications. As an example, phthalimide derivatives were found to be effective photo-responsive n-type organic semiconductors because of ICT contribution.…”
Section: Introductionmentioning
confidence: 99%